1995
DOI: 10.2307/30141094
|View full text |Cite
|
Sign up to set email alerts
|

Containment of Pertussis in the Regional Pediatric Hospital during the Greater Cincinnati Epidemic of 1993

Abstract: Control measures appeared effective. Pertussis occurred in 87 (2%) employees. Among 102 children hospitalized with pertussis, respiratory isolation was delayed in nine cases, and one case was nosocomial. Program expenses totalled $85,400. Adult booster immunization with acellular pertussis vaccine might represent the safest and least expensive strategy for preventing epidemic pertussis, and controlled trials of acellular pertussis vaccine in hospital employees are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…B. pertussis outbreaks in HCWs, however, occur commonly (31)(32)(33)(34)(35). In addition, occupational infection with C. pneumoniae and M. pneumoniae has been reported in HCWs (36,37).…”
Section: Discussionmentioning
confidence: 97%
“…B. pertussis outbreaks in HCWs, however, occur commonly (31)(32)(33)(34)(35). In addition, occupational infection with C. pneumoniae and M. pneumoniae has been reported in HCWs (36,37).…”
Section: Discussionmentioning
confidence: 97%
“…HCWs with pertussis were assumed to have additional lost work, because infection-control policies recommend that symptomatic HCWs be furloughed for 5 days while taking antibiotics [53]. Up to 20% of symptomatic HCWs are furloughed, so we assumed as a base case that 20% of HCWs lose 5 days from work and that the remaining 80% of HCWs lose no time from work [44]. Our low estimate of the HCW symp- tomatic pertussis furlough rate was 10%, and the high estimate was 30%.…”
Section: Methodsmentioning
confidence: 99%
“…The degree of improvement with the sign and dispenser combination over the dispenser was not statistically significant. 1995 Christie et al 19 Overview Compliance with gown use among visitors was low (65%) though higher among visitors to patients in ICUs than in general wards (OR, 10; 95% CI, 6.0-17.0). In the ICU, gown use was highly predictive of glove use.…”
Section: The Extent Of Contact Between Visitors and Patients Likely Vmentioning
confidence: 99%
“…A literature review identified 6 articles surveying various aspects of visitors and respiratory precautions. [15][16][17][18][19][20] All studies were small and observational or cross-sectional by design. Of these 6 studies, 3 consisted of surveys, 15,16,18 1 study included direct observation, 17 and 2 studies described procedures during outbreak settings.…”
Section: Visitors and Respiratory Isolation Precautionsmentioning
confidence: 99%
See 1 more Smart Citation